THE ROLE OF INTEREST RATE MODERATION IN THE RELATIONSHIP OF INVESTMENT DECISIONS, AND FUNDING DECISIONS TO COMPANY VALUE - Mianika, Riani; Wulandari, Ika (Proceeding Kilisuci International Conference on Economic & Business, 2023)
Research aim : The purpose of this study was to examine the effect of investment decisions and funding decisions on firm value and the moderating relationship of interest rates in influencing the strength or weakness of the relationship between investment decisions and funding decisions on firm value. Design/Methode/Approach : This study used a sample of property and real estate sector companies listed on the Indonesia Stock Exchange during 2019-2021 as many as 7 companies with a total sample of 84 financial reports obtained using the purposive sampling method. The analysis method used is multiple linear regression and Moderated Regression Analysis (MRA) with the analysis tool IMB SPSS ver.21. Research Finding : Based on the study's results, investment decisions are positively but insignificantly affecting firm value, while funding decisions significantly negatively impact firm value, interest rates do not moderate the relationship between investment decisions and firm value, and interest rates do not moderate the relationship between funding decisions and firm value. Theoretical contribution/Originality : The objective of this study was to investigate whether or not interest rates influence the weak or strong relationship between investment decisions and funding decisions and company value, and to determine whether or not interest rates play a role Practitionel/Policy implication : - Research limitation : The research only focuses on property and real estate sector companies listed on the Indonesian IDX in 2019-2021